Proteksi Ekstrak Rimpang Pacing Terhadap Resistensi Insulin pada Model Hewan yang Diinduksi Pakan Tinggi Lemak Dan Fruktosa - Aulia Nurfazri Istiqomah, Aulia Nurfazri Istiqomah; Kharina Septi Lestari; Imas Fauzya Zahra (Akademi Farmasi Yarsi Pontianak, 2024)
Insulin resistance is a condition where the sensitivity of cells or tissues to insulin decreases, which is one of the main factors causing type 2 diabetes mellitus. Current diabetes therapy is still limited to synthetic drugs which can cause side effects, so alternative diabetes therapy is being sought. using natural materials, one of which is using pacing. The pacing rhizome plant contains the compound diosgenin which has antidiabetic properties. This study aims to determine the activity of ethanol extract of pacing rhizomes in increasing insulin sensitivity and the effective dose in increasing insulin sensitivity. Testing was carried out preventively using an animal model of insulin resistance induced by high fat and fructose feed orally for 42 days. The test animals were divided into six groups, namely normal, induction, comparison metformin 45 mg/KgBW, ethanol extract of rhizome pacing (EERP) dose 150 mg/KgBW, 300 mg/KgBW and 450 mg/KgBW. The parameters measured were blood glucose levels and insulin tolerance test constants. From the research results, it was found that ethanol extract of pacing rhizome at a dose of 300 mg/KgBW could increase insulin sensitivity. Keywords: insulin resistance, pacing, blood glucose levels, Costus speciosus